Optical Internal Urethrotomy for Urethral Stricture Under a New Local Anaesthesia Technique (Bangladesh Journal of Urology, 2020)
Objectives: To determine the feasibility of routinely performing internal optical urethrotomy for anterior urethral stricture under intracorpus spongiosum anesthesia in an outpatient setting.Methods. In this prospective study a consecutive series of 34 patients with anterior urethral stricture, a dosage of 3 mL of 1% lidocaine was slowly injected into the glans penis. Next, optical urethrotomy was performed immediately with a cold-cutting knife. The effect of this anesthetic technique was evaluated by questionnaire.Results. Internal urethrotomy was successfully completed in all the patients. Thirty-two patients (94.12%) had no pain or discomfort. Two patient reported minimal but tolerable discomfort while the tissue above the stricture was being cut. The anesthesia lasted for about 1.5 hours and was very satisfactory without any complications.Conclusions. Under intracorpus spongiosum anesthesia, optical urethrotomy can be routinely performed in an outpatient setting. With this new local anesthesia, internal urethrotomy is a safe, effective, simple, and inexpensive procedure for treatment of anterior urethral stricture.Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.64-66